THE EFFECT OF TURMERIC LEAF EXTRACT (Curcuma domestica) IN DRINKING WATER ON PHYSICAL QUALITY OF LOHMANN BROWN’SEGG - M.R., Dharmayanti; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to examine the effect of turmeric leafextract ( Curcuma domestica Val.) in drinking water on the physical quality of Lohmann Brown’segg. Completely Randomized Design (CRD) was used with three treatments. Each treatment was repeated six times usethree of hen bird of 60 weeks aged perspectively. The three treatments were K0 that is Lohmann Brown was given drinking water without water extracts turmeric leaf; K1 that is Lohmann Brownwas given an additional 2% of extracts turmeric leaf; K2 Lohmann Brown was given an additional 4% of extracts turmeric leaf.The variables in this study included the average of egg weight, percentage of albumen, percentageof egg yolk, percentage ofeggshell, eggshell thickness, and egg index. The results showed that the average of egg weight, percentage of egg yolk, percentage of eggshell, and eggshell thicknesswere highly significantdifferent (P<0,05) and the percentage of albumen wassignificant different (P<0,05) lower than control.The percentage of egg yolk with level 4% did not significantly different (P>0,05) from control and also from level 2%.Based on the results concluded that turmeric leaf extract at level 2% can increase average of egg weight, percentage of egg yolk, percentage of eggshell, eggshell thickness, decrease the percentage of albumen, but none effect of the egg index. Level 4% of turmeric leaf extract can increase the average egg weight, percentage of eggshell, eggshell thickness, decrease in the percentage of egg white, but none effect of the percentage of egg yolk and index. Keywords: Lohmann Brown, Curcuma domestica Val. , egg